USING 3D MOLECULAR STRUCTURE SIMULATION IN DEVELOPING CHEMISTRY COMPETENCE IN STUDENTS (Universal International Scientific Journal, 2026)
The spatial structure of organic compounds (3D molecular structure) is an important tool in teaching organic chemistry. In this study, 16 3D molecular structures of hydrocarbons and chemical reaction simulations were developed and lesson plans for teaching the topic of alkenes were developed based on them. Teachers were given instructions on how to use these lesson plans, and tests were developed to assess students' chemistry competencies. The main objective of the study was to determine the impact of using 3D molecular structure simulations on the development of chemistry competencies in students. The research methodology was conducted with the participation of 30 students, who were divided into an experimental group and a control group. The results of the study showed the effectiveness of 3D molecular structure simulation, including: students' chemical competence increased, the transfer and application of spatial chemistry concepts to higher-level knowledge developed, and the possibilities for planning the nature and mechanisms of chemical reactions expanded. As a result, chemistry teachers can effectively use 3D molecular structure simulations in teaching topics such as atomic radius, bond length, and bond angle.
Keywords: simulation; 3D molecular structure; chemistry competence,